Analysis of Entrepreneurial Characteristics and Competitive Advantage on MSME Performance: A Study of GrabFood-Based Padang Restaurants in Sukabumi City - Ramdhani, Adik Anov Permana; Nurmala, Resa; Saori, Sopyan (JURNAL MANAJEMEN MOTIVASI, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, particularly in the culinary sector, such as Padang restaurants. In the digital era, platforms like GrabFood have become catalysts for enhancing MSME performance. This study aims to analyze the influence of entrepreneurial characteristics and competitive advantage on the performance of Padang restaurants registered as GrabFood merchants in Sukabumi City. A quantitative approach was employed, using descriptive and associative methods, with a sample of 30 respondents from a total population of 34 restaurants. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression, as well as validity, reliability, and classical assumption tests. The findings indicate that both entrepreneurial characteristics and competitive advantage significantly affect MSME performance, both partially and simultaneously. GrabFood has been proven to support increased sales and market reach for MSMEs. The study concludes that strengthening entrepreneurial characteristics—such as commitment and innovation—along with competitive advantage through quality and efficiency, can optimize MSME performance within the digital ecosystem. Practical implications include recommendations for entrepreneurship training and the optimization of digital platform features for MSMEs.